AGNIDAGDHA - A REVIEW IN SUSHRUTASAMHITA - Dighe sujata Yashwant; Banarase Madhavi; Deshpande B.N. (International Journal of Applied Ayurved Research, 2016)
Sushruta is pioneer of Indian surgery. He explained Agni Dagdha (burn) and its management in 12th Adhyaya of Sutrasthana. In this present era, due to industrialization, incidences of burn wound are increased. In day to day life, we used to come across various types of burns due to fire, moist heat, chemicals, electrical etc. As the patient of Dagdha (Burn) are in-creasing in the society. Sushruta explained Angnidagdha in detail, causes, types, signs and its management. Traditional medicines plays important role in this kind of wounds.